Association between the use of mobile touchscreen devices and the quality of parent-child interaction in preschoolers - Liszkai-Peres, Krisztina; Budai, Zsófia; Kocsis, Adrienn; Jurányi, Zsolt; Pogány, Ákos; Kampis, György; Miklósi, Ádám; Konok, Veronika (Frontiers in Child and Adolescent Psychiatry, 2024)
The early use of mobile touchscreen devices (MTSDs), including smartphones and tablets, may reduce the frequency and quality of social interactions between children and parents, which could impact their relationship and have negative consequences on children's socio-cognitive development. In this study, we applied a parental questionnaire and a behavioral observational method in a laboratory setting (free and structured play sessions) to examine the association between preschool MTSD use and the quantity and quality of parent–child relationships. Our findings revealed that preschoolers who regularly use MTSDs (n = 47, aged 4–7 years, engaging in MTSD use for at least 2 h per week) are spending less time with their parents and exhibited lower quality interactions compared to non-users (n = 25). However, shared offline leisure time with parents serves as a protective factor among MTSD-users. Furthermore, our study demonstrated a positive association between parents' and children's media use. The results suggest that preschool MTSD use may have unfavorable effects on parent–child interactions, both in terms of quantity and quality. Alternatively, lower quantity and quality of parent–child interaction may lead to higher MTSD use in the child. Based on the results, the importance of engaging in sufficient offline family interactions besides digital media use should be emphasized to parents of preschoolers, and health organizations and governments should include this in their recommendations and policies concerning childhood digital media use.